2015
DOI: 10.1103/physrevlett.115.264503
|View full text |Cite
|
Sign up to set email alerts
|

Condensation of Coherent Structures in Turbulent Flows

Abstract: Coherent structures are ubiquitous in turbulent flows and play a key role in transport. The most important coherent structures in thermal turbulence are plumes. Despite being the primary heat carriers, the potential of manipulating thermal plumes to transport more heat has been overlooked so far. Unlike some other forms of energy transport, such as electromagnetic or sound waves, heat flow in fluids is generally difficult to manipulate, as it is associated with the random motion of molecules and atoms. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 21 publications
4
83
0
Order By: Relevance
“…Special attention is paid to the abnormal Ra dependence of flatness in the Γ = 0.1 cell, which is also reflected in its very different time series signals and the bimodal shaped PDF at Ra = 8.6 × 10 7 . Based on the recent finding by Chong et al (2015), these strange behaviours for Γ = 0.1 could be due to the fact that the LSC no longer exists in this case.…”
Section: Local Temperature Fluctuationsmentioning
confidence: 74%
“…Special attention is paid to the abnormal Ra dependence of flatness in the Γ = 0.1 cell, which is also reflected in its very different time series signals and the bimodal shaped PDF at Ra = 8.6 × 10 7 . Based on the recent finding by Chong et al (2015), these strange behaviours for Γ = 0.1 could be due to the fact that the LSC no longer exists in this case.…”
Section: Local Temperature Fluctuationsmentioning
confidence: 74%
“…As the strengths of stabilization increase, the global transport behaviour undergoes a transition from a typical RB regime to the regime dominated by the stabilizing force. However, earlier studies in CRB [22,24], RRB [26,27] and DDC [30,35] separately revealed an intermediate regime with enhancement in scalar transport, and in CRB and DDC even the decoupling of scalar and mass transport was observed. Figures 1(a,b,c) show the normalized N u against 1/Γ for CRB, 1/Ro for RRB, and Λ for DDC, respectively.…”
mentioning
confidence: 69%
“…In CRB, it is the reciprocal of the width-to-height ratio 1/Γ that characterizes the relative strength of stabilizing [22][23][24]. In RRB, the stabilization is characterized by the ratio of Coriolis force to buoyancy which is the reciprocal Rossby number 1/Ro [25][26][27][28].…”
mentioning
confidence: 99%
“…In [22] by example of P r = 4.3 it was shown that the optimal aspect ratio Γ opt , which provides the maximal N u, exists for any Ra. The present results suggest that the optimal Γ opt also exists for any P r. This fact is very important for optimization of heat transport in practical applications.…”
Section: Numerical Methods and Simulation Parametersmentioning
confidence: 99%